Analisis Nilai Manfaat Ekonomi Program CSR dan PKBL PT. Bukit Asam (Tbk.) - Rabin Ibnu Zainal (MBIA, 2018)
Corporate Social Responsibility (CSR) is a form of social responsibility from the business to also care about the conditions of the social environment around it. In this concept, businesses are not only required to realize their economic responsibilities in fulfilling the production of goods and services but are also asked to care about aspects of social and environmental responsibility affected by these production activities. PT. Bukit Asam (Tbk) (PTBA) as one of the companies engaged in coal mining in Muara Enim district, is also inseparable from the responsibilities that have been mandated in the form of related regulations and laws. PTBA as a BUMN is also mandated to implement the Partnership and Community Development Program (PKBL), which is also a form of CSR programs. In its implementation, if it is associated with the mandate of CSR and PKBL regulations, it is appropriate for the CSR-PKBL program not only to measure its business benefits, both in terms of the company's reputation, but also to continue to operate to the marketing aspects. However, CSR and PKBL must be able to provide economic benefits to the recipient community. For this reason, this study presents how the perspective of the community in seeing the CSR-PKBL program that has been conducted by PTBA to the community in Muara Enim Regency. The study was conducted in communities in 17 villages in 3 sub-districts identified as having received the CSR-PKBL program from 2014-2015. This study is useful for companies to provide a direction to the future CSR-PKBL program, and also to local governments to formulate policies related to the implementation of CSR-PKBL as mandated by law.